(untitled) (Nepalese Journal of Management Research, 2024)
Investment refers to the expenditure made on physical and human capital and is one of the components of gross domestic product by expenditure method. Multiplier effect explains the extent by which national income changes due to the change in the investment. This study aims to find out the relationship between total investment and economic growth and further estimates the multiplier coefficient of investment in Nepalese economy using linear regression model taking time series data from FY 2002/03 to FY 2022/23. Gross domestic product is the dependent variable and gross capital formation is an independent variable. The secondary data is collected from the publications of Nepal Rastra Bank is processed and analyzed by using SPSS statistical software. Gross capital formation of Nepal in that period represents the total investment. From the analysis of collected data, it is observed that there is positive and significant relationship between gross capital formation and gross domestic product. The estimated multiplier coefficient of investment is found to be 2.645 (t-value = 23.772; p-value <0.001).